Phosphoserine Phosphatase Is Required for Serine and One-Carbon Unit Synthesis in Hydrogenobacter thermophilus - Kim, Keugtae; Chiba, Yoko; Kobayashi, Azusa; Arai, Hiroyuki; Ishii, Masaharu (Journal of bacteriology, 2017)
Hydrogenobacter thermophilus is an obligate chemolithoautotrophic bacterium of the phylum Aquificae and is capable of fixing carbon dioxide through the reductive tricarboxylic acid (TCA) cycle. The recent discovery of two novel-type phosphoserine phosphatases (PSPs) in H. thermophilus suggests the presence of a phosphorylated serine biosynthesis pathway; however, the physiological role of these novel-type metal-independent PSPs (iPSPs) in H. thermophilus has not been confirmed. In the present study, a mutant strain with a deletion of pspA , the catalytic subunit of iPSPs, was constructed and characterized. The generated mutant was a serine auxotroph, suggesting that the novel-type PSPs and phosphorylated serine synthesis pathway are essential for serine anabolism in H. thermophilus. As an autotrophic medium supplemented with glycine did not support the growth of the mutant, the reversible enzyme serine hydroxymethyltransferase does not appear to synthesize serine from glycine and may therefore generate glycine and 5,10-CH 2 -tetrahydrofolate (5,10-CH 2 -THF) from serine. This speculation is supported by the lack of glycine cleavage activity, which is needed to generate 5,10-CH 2 -THF, in H. thermophilus . Determining the mechanism of 5,10-CH 2 -THF synthesis is important for understanding the fundamental anabolic pathways of organisms, because 5,10-CH 2 -THF is a major one-carbon donor that is used for the synthesis of various essential compounds, including nucleic and amino acids. The findings from the present experiments using a pspA deletion mutant have confirmed the physiological role of iPSPs as serine producers and show that serine is a major donor of one-carbon units in H. thermophilus . IMPORTANCE Serine biosynthesis and catabolism pathways are intimately related to the metabolism of 5,10-CH 2 -THF, a one-carbon donor that is utilized for the biosynthesis of various essential compounds. For this reason, determining the mechanism of serine synthesis is important for understanding the fundamental anabolic pathways of microorganisms. In the present study, we experimentally confirmed that a novel phosphoserine phosphatase in the obligate chemolithoautotrophic bacterium Hydrogenobacter thermophilus is essential for serine biosynthesis. This finding indicates that serine is synthesized from an intermediate of gluconeogenesis in H. thermophilus . In addition, because glycine cleavage system activity and genes encoding an enzyme capable of producing 5,10-CH 2 -THF were not detected, serine appears to be the major one-carbon donor to tetrahydrofolate (THF) in H. thermophilus .